2012
DOI: 10.1104/pp.111.186866
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of 9-cis-Epoxycarotenoid Dioxygenase, Which Encodes a Key Enzyme in Abscisic Acid Biosynthesis, Alters Fruit Texture in Transgenic Tomato    

Abstract: Cell wall catabolism during fruit ripening is under complex control and is key for fruit quality and shelf life. To examine the role of abscisic acid (ABA) in tomato (Solanum lycopersicum) fruit ripening, we suppressed SlNCED1, which encodes 9-cisepoxycarotenoid dioxygenase (NCED), a key enzyme in the biosynthesis of ABA. To suppress SlNCED1 specifically in tomato fruits, and thus avoid the pleiotropic phenotypes associated with ABA deficiency, we used an RNA interference construct driven by the fruit-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(186 citation statements)
references
References 110 publications
9
174
0
3
Order By: Relevance
“…Clade A PP2Cs function as negative regulators of the ABA signalling pathway and their transcript levels are highly induced by ABA in plants (Merlot et al, 2001;Saez et al, 2004;Saez et al, 2006;Yoshida et al, 2006b;Xue et al, 2008;Li et al, 2009) Fig.1 and 4A, Results Chapter 1), which agreed with results reported in harvested grapes and tomatoes (Sun et al, 2010;Sun et al, 2012a;Sun et al, 2012b) and in vegetative tissues (Tan et al, 2003;Loyola et al, 2012;Frey et al, 2012). Interestingly, CsNCED1 followed an expression pattern highly similar to that displayed by the members of the CsPP2CA family in citrus fruit (Fig.2, Results Chapter 3).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Clade A PP2Cs function as negative regulators of the ABA signalling pathway and their transcript levels are highly induced by ABA in plants (Merlot et al, 2001;Saez et al, 2004;Saez et al, 2006;Yoshida et al, 2006b;Xue et al, 2008;Li et al, 2009) Fig.1 and 4A, Results Chapter 1), which agreed with results reported in harvested grapes and tomatoes (Sun et al, 2010;Sun et al, 2012a;Sun et al, 2012b) and in vegetative tissues (Tan et al, 2003;Loyola et al, 2012;Frey et al, 2012). Interestingly, CsNCED1 followed an expression pattern highly similar to that displayed by the members of the CsPP2CA family in citrus fruit (Fig.2, Results Chapter 3).…”
Section: Discussionsupporting
confidence: 82%
“…NCED gene was silenced by RNAi in strawberry fruit reducing ABA levels, which impaired response of ABA-downstream signalling genes and showed uncoloured phenotype that was rescued by exogenous treatment with the hormone . By using the same strategy Sun et al (2012a) reduced NCED activity, which led to down regulation of major genes encoding cell wall catabolic enzymes in tomato. It has been also demonstrated that ABA-deficiency in sitiens tomato mutant fruit (Tal and Nevo, 1973;Taylor and Tarr, 1984) led to increased cuticle permeability, which was correlated with disease resistance (Curvers et al, 2010).…”
Section: Physiological Effects Of the Aba Deficiencymentioning
confidence: 99%
“…Fleshy fruit ripening is determined both by internal regulators, such as phytohormones and signaling proteins, and external environmental cues (Ulrich, 1958;Giovannoni, 2001;Llop-Tous et al, 2002;Owen et al, 2009;Giribaldi et al, 2010;Hirayama et al, 2010;Koyama et al, 2010;Gagné et al, 2011;Sun et al, 2012;Yang et al, 2012;Seymour et al, 2013). Temperature, photon flux density, and water availability affect both fruit ripening and quality, and temperature is particularly important for controlling the progression of fruit development and ripening during fruit production.…”
mentioning
confidence: 99%
“…The fact that SlMIXTA-RNAi lines displayed downregulation of the ABA biosynthesis gene NINE-CIS-EPOXYCAROTENOID DIOXYGENASE1 (Sun et al, 2012;Ji et al, 2014) suggests that the reason for the increased susceptibility to dehydration may be caused by the impairment of a signal originating from the cuticle (Supplemental Fig. S4; Supplemental Data Set S2).…”
Section: Slmixta-like Regulates Postharvest Water Loss Prevention Andmentioning
confidence: 99%